36. Bilateral loss of cortical SEPs predict severe MRI lesions in neonatal hypoxic ischemic encephalopathy treated with hypothermia. Issue 12 (December 2017) - Cione, G.; Cainelli, E.; Cappellari, A.; Di Capua, M.; Janes, A.; Pro, S.; Vittorini, R.; Manara, R.; Suppiej, A.
Abstract : The introduction of therapeutic hypothermia for neonatal hypoxic-ischemic encephalopathy call for reevaluation of the prognostic role of SEPs. This study aimed to test the prognostic value of SEPs using as outcome measure MRI severity and patterns of injury. Neonates eligible for hypothermia were recruited from four Italian Centers if they performed SEP and MRI at 4–15 days of life. SEPs were scored as: normal (bilaterally recorded/unilaterally absent N20) or altered (bilaterally absent N20). The severity of brain injury was measured using a validated MRI scoring system for acute and sub-acute signal abnormalities. 58 neonates were included in the analysis. Bilaterally absent N20 was observed in 10/58 (17%); all had moderate/severe MRI abnormalities. Furthermore, 37 infants (62%) had normal MRI all with normal N20. The positive predictive value of SEP on MRI outcome was of 100%, while the negative predictive value 72%, sensitivity 43%, specificity 100%, with an accuracy of 78% (p < .001). Bilateral absence of cortical SEPs is associated with a moderate/severe MRI pattern of injury, as previously reported in non-cooled infants. The prognostic value of SEPs is not (or minimally) affected by hypothermia.